2021
DOI: 10.1177/1093526620986492
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid Sarcoma Arising in a Long-Term Survivor of an Atypical Teratoid/Rhabdoid Tumor in a Patient With Rhabdoid Tumor Predisposition Syndrome

Abstract: Rhabdoid tumor predisposition syndrome (RTPS) is defined as the presence of a SMARCB1 or SMARCA4 genetic aberration in a patient with malignant rhabdoid tumor. Patients with RTPS are more likely to present with synchronous or metachronous rhabdoid tumors. Based on the current state of rhabdoid tumor taxonomy, these diagnoses are based largely on patient demographics, anatomic location of disease, and immunohistochemistry, despite their nearly identical histologic and immunohistochemical profiles. Thus, the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In contrast to EHE, epithelioid sarcoma cells can express epithelial markers such as AE1/AE3 and epithelial membrane antigen (EMA), and the expression of INI1 is often absent. [ 21 - 24 ]…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In contrast to EHE, epithelioid sarcoma cells can express epithelial markers such as AE1/AE3 and epithelial membrane antigen (EMA), and the expression of INI1 is often absent. [ 21 - 24 ]…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Biallelic-inactivating SMARCB1 mutations are the most frequent aberration. Nonsense frameshift and splice site mutations complete the causes of SMARCB1 loss, but these are quite rare [ 62 , 63 , 64 ]. Preclinical data have suggested that some miRNAs (miR-193a-5p, miR-206, miR-381, miR-671-5p) are involved in SMARCB1 inactivation through epigenetic mechanisms [ 65 , 66 , 67 ].…”
Section: Rhabdoid Tumors Associated With Swi/snf Complex Alterationsmentioning
confidence: 99%
“…A case of homozyogously deleted ES occurring in the setting of SMARCB1 constitutional deletion was reported by Le Loarer and coworkers in a 25-year-old ES patient without prior familial or personal history of cancer [ 57 ]. More recently, an ES arisen in a patient affected by a rhabdoid tumor predisposition syndrome due to a constitutional intron/exon SMARCB1 variant (c.501-1G > A), likely responsible for aberrant mRNA splicing, has been documented [ 60 ].…”
Section: Smarcb1 Loss An Es Molecular Hallmarkmentioning
confidence: 99%